Genska zdravila - Mlinarič-Raščan, Irena (Farmacevtski vestnik, 2005)
Gene-based medicines are therapeutic modalities of recombinant nucleic acids capable of interfering with gene function either by replacing its function orby silencing it. The main advantage of gene-based medicines is in targeting a molecular defect of treated pathogenesis. Current methods of gene delivery are still inadequate for successful applications and high efficiencies, causing unwanted toxicity and immune reactions. Genetic disorders that arise from mutations in a single gene are the best candidates for gene therapy. Despite this, recent developments of gene therapy are largely focused on treatment of complex disorders with combined effects of variations in many genes such as cancer, immune dysfunctions and neurodegenerative disorders. Modulation of gene function in geriatric population is intended to improve thequality of life of older persons. Gene therapy of Alzheimerćs disease attracts a vast interest of researchers as well as geriatric population.
Keywords: Alzheimerjeva bolezen; genska zdravila